A bibliometric analysis on working capital management in SME - Amram, Nor Razuana; Zainudin, Noor Hidayah; Wan Azman, Nazihah; Ghazali, Nuur Atikah (Universiti Teknologi MARA, Kedah, 2025)
Bibliometrics involves combining, analyzing, and examining bibliographic information from scientific publications. This study aims to analyze the clusters of Working Capital Management (WCM) in Small and Medium-sized Enterprises (SMEs) using VOSviewer software. The study reviewed articles on WCM in SMEs published from 2007 to May 2024 in the Scopus database, applying well-established bibliometric techniques and analyzing the data using VOSviewer software. Consequently, 21 articles published in the past decade were evaluated by analyzing trends in publications, authors, affiliated organizations, countries, cited articles, and popular themes to understand the research topics researchers have focused on in recent years. Surprisingly, this study's results reveal minimal collaboration between authors, universities, and countries working on the topic of WCM. In conclusion, bibliographic analysis can provide fundamental insights into research on WCM in SMEs. By applying bibliographic analysis to WCM in SMEs, this study helps contribute to scientific journals, academics, and institutions in understanding and promoting research on this topic in the field of education. ©2025 UiTM Kedah. All rights reserved.